Ultrasound-guided single-shot preemptive erector spinae plane block for postoperative pain management - Çiftçi, Bahadır; Ekinci, Mürsel; Demiraran, Yavuz (W B Saunders Co-Elsevier Inc, 2019)
Thoracotomy is a procedure that causes severe pain as a result of muscle incision, retraction of the ribs, and damage to the intercostal nerves. Postoperative analgesia management is very important for respiratory functions, and successful pain management reduces postoperative complications and length of hospital stay.1 A variety of procedures have been described for the first-step treatment of thoracic analgesia, including intercostal nerve blocks, thoracic epidural analgesia (TEA), and thoracic paravertebral blocks.2 However, their usage is limited because of complications and failure rates (up to 15% in TEA).3 The other option for analgesia is intravenous opioid medications that can be used in combination with nonsterioidal anti-inflammatory drugs.4 Adverse effects such as sedation, hypoventilation, nausea, and vomiting can occur, especially in systemic high opioid doses used for severe pain such as after thoracotomy.
WOS: 000463691000052
PubMed ID: 30477888
Keywords: Ultrasound-Guided; Pain Management; Erector Spinae Plane Block